Analysis Of Mathematical Communication Skills On The Material Of Two-Variable Linear Equation System In Smp Negeri 7 Medan - Adi Suarman Situmorang; Enjelika Pandiangan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study was to describe the mathematical communication skills of class VIII students of a two-variable linear equation system at UPT SMP Negeri 7 Medan. The type of research used is descriptive qualitative. The samples taken in this study using purposive sampling were students at UPT SMP Negeri 7 Medan, namely class VIII. The instrument used in this research is a test of mathematical communication skills in the form of 4 essay questions. Data collection techniques using triangulation techniques, followed by data analysis which includes data collection, data reduction, data presentation, and drawing conclusions. The results of student tests that have been carried out on the material of mathematical communication skills show that most students meet the indicators of mathematical communication skills. So, it can be concluded that this study shows that the overall mathematical communication ability of students is relatively high, this can be seen from the results of mathematical communication skills at the high category level of 53%, the level of the medium category of 31%, and the level of the medium category of 31%. the low category rate is 16%.